THE USE OF HUMOR IN TEACHING ENGLISH FOR NURSING TO IMPROVE STUDENTS’ SPEAKING SKILL WITH HIGH OR LOW LEARNING MOTIVATION - Ahmad Nur syafiq (Universitas Muhammadiyah Semarang, 2015)
This study aimed at investigating the effectiveness of humor as English foreign language teaching material to improve students’ speaking skill with of high or low motivation for the students and the effect that the use of humor gives to their teaching. Furthermore, this study was quasi experimental research named two-way (two-by-two) factorial design. The population of this study was the fourth semester Students of S1 Nursing Science Program of STIKES Muhammadiyah Kudus which covered 125 students. 80 students, later on, were choosen to be a sample, 40 as experimental group and 40 as control group. Both groups were distributed the pre-test to measure students' speaking skill. For treatment, Shade's (1996) classification of verbal humor was used. It means that the teacher in experimental group used humorous materials such as jokes, riddles and anecdotes related to the topics in each part of the lesson, during the warm up, discussing the topic and teaching new words. While in control groups used story telling material based on his or her life best experience. After 3 times treatments, both groups were distributed the post-test. The results of this quantitative study revealed that humor as teaching material has significant effect on the students’ speaking skill to those who have high and low learning motivation the way that fourth semester Students of S1 Nursing Science Program of STIKES Muhammadiyah Kudus expressed that humor in the classroom situation affected their learning positively to those who have high or low motivation rather than conventional material. Further study may also be conducted to determine whether teachers’ use of humor appears to reduce student anxiety and stress in the classroom to improve students’ speaking skill, retention, and student-teacher relationships. Since a small number of subjects were involved in this study, the results may not necessarily be extended to make a prediction about the entire population.Key words: students’ learning motivation, Humor material, Speaking skill.